(untitled) (Research, Society and Development, 2022)
The work was carried out with the aiming of evaluating the intensity of defoliation, return rate and structural characteristics of millet (Pennisetum americanum (L.) Leeke) grazed by beef heifers in two phenological stages of this forage. The grazing method with continuous stocking and variable number of animals was used to maintain the canopy height between 30 and 40 cm. The experimental design used was completely randomized with two phenological stages, vegetative and pre-reproductive, with eight area replications. The total number of leaves was 21.8% higher in the vegetative phase. The population density of basal (116.0/m²) and axillary (101.4 tillers/m²) tillers was similar in the stages. The mean defoliation intensity was 47% and the overall rate of return was 5.6 days. Each heifer grazed an area of 395.3 m²/day. Leaf blades were grazed 4.7 times during leaf life and the thermal accumulation observed between defoliation intervals was sufficient for 1.2 new leaves to be emitted before the next defoliation event. The heifers maintained a similar grazing strategy during the evaluated stages with similar defoliation intensity and return rate of expanded and expanding leaves.